Penggunaan Media Audio Visual untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Katolik Nabutaek - Martha Khristina Kota; Gaspar Melo; Maria Verena Seran (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the use of audio-visual media to improve learning outcomes for fourth grade students at Nabutaek Catholic Elementary School. The research subjects consisted of 24 people. This type of research is Classroom Action Research with data collection methods using tests and observation sheets. The results of the study show that learning using audio-visual media is proven to improve student learning outcomes. Teacher performance in cycle I was in the good category, namely 77.14%, increased again in cycle II to be in the very good category, namely, 89.81%. Student activity also increased from cycle I to cycle II, namely in cycle I students were in the good category, namely 72.09%, increasing again in cycle II, in the very good category, namely 93.37%. Likewise, the acquisition of test results also experienced an increase in learning outcomes, namely in cycle I the results of the classical learning mastery test were 54.16% in the sufficient category and experienced an increase in cycle II in the very good category with 91.66% classical learning completeness. Therefore it can be concluded that the use of audio-visual media can improve student learning outcomes on natural resource material for class IV Nabutaek Catholic Elementary School.